Mathematical Problem Solving Capabilities: The Impact of Search Solve Create Share and Think Pair Share learning models on Logarithmic Lesson - Purnama, Syahfitri; Muawanah, Muawanah; Surati, Tista Maya; Septianingsih, Rika (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
A learning can run well supported by an appropriate learning model. In this study the Search Solve Create Share (SSCS) and Think Pair Share (TPS) learning models are used. This research is a quantitative study using t test. The purpose of this study is to study whether there are differences between the SSCS learning model and the TPS learning model on students' mathematical problem solving abilities. This research is a quantitative study with a research design. Random Design Group Pretest-Posttest Group. The results of this study obtained a P-value smaller than the significance level. Hypothesis testing from this study provides conclusions about the TPS learning model better than the SSCS learning model in improving students' mathematical problem solving abilities.